2012
DOI: 10.3390/ijerph9082742
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Trust in Messages, Risk Perception, and Risk Reduction Preferences Based upon Avian Influenza in Taiwan

Abstract: Improvements in communications technology enable consumers to receive information through diverse channels. In the case of avian influenza, information repeated by the mass media socially amplifies the consumer awareness of risks. Facing indeterminate risks, consumers may feel anxious and increase their risk perception. When consumers trust the information published by the media, their uncertainty toward avian influenza may decrease. Consumers might take some actions to reduce risk. Therefore, this study focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…They have suggested that relational trust is a more powerful predictor of compliance with recommended behaviors than calculative trust, particularly in an unknown situation. Because of the high degree of uncertainty surrounding a new type of influenza, people typically do not demonstrate the ability to fully process messages from the government [31]. People must make quick judgments, based on emotion and a general feeling toward the government, in taking action.…”
Section: Discussionmentioning
confidence: 99%
“…They have suggested that relational trust is a more powerful predictor of compliance with recommended behaviors than calculative trust, particularly in an unknown situation. Because of the high degree of uncertainty surrounding a new type of influenza, people typically do not demonstrate the ability to fully process messages from the government [31]. People must make quick judgments, based on emotion and a general feeling toward the government, in taking action.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this study, the degree of reduction of depression and improvement of care quality are possible indicators. Together, PU, PEOU, and PPR accounted for 57.7% of the variance of BI to use PHR, implying that other factors, such as trust perception [ 73 ], which can promote the use) of TAM in the field of healthcare, should be sought. Moreover, recruiting various types of patients is recommended to increase the representativeness and generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals within specific communities-whether related to one's documentation status, structural racism, economic disparities, or cultural background-have pre-existing belief systems, and therefore specific counter-messages, specifically targeted to address the belief system held by members of this community, may be most effective at enhancing vaccine uptake. Trust-based messaging rather than those that are fear-inducing, from community members and key community stakeholders may be valuable catalysts for promoting the adoption and uptake of vaccines [10,11]. Consideration of why individuals possess anti-vaccine beliefs and designing targeted messages to combat those beliefs, may be instrumental in ultimately shifting individuals' risk assessment.…”
Section: Encouraging Acceptability Of the Vaccinementioning
confidence: 99%